1997
DOI: 10.1002/pro.5560060605
|View full text |Cite
|
Sign up to set email alerts
|

De novo design of the hydrophobic core of ubiquitin

Abstract: We have previously reported the development and evaluation of a computational program to assist in the design of hydrophobic cores of proteins. In an effort to investigate the role of core packing in protein structure, we have used this program, referred to as Repacking of Cores (ROC), to design several variants of the protein ubiquitin. Nine ubiquitin variants containing from three to eight hydrophobic core mutations were constructed, purified, and characterized in terms of their stability and their ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
149
2
3

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(157 citation statements)
references
References 66 publications
3
149
2
3
Order By: Relevance
“…A more common approach includes additional discrete rotamers at de®ned increments, for example at AE 15 or AE one standard deviation from the statistically derived rotamer value (Dahiyat & Mayo, 1996;Tuffery et al, 1991). For our analysis, we have also used a version of our ®xed backbone algorithm that incorporates a wide range of¯exibility into the side-chains, with ®ne sampling of side-chain dihedral angles (5 ) at almost all possible angles (Lazar et al, 1997). An analysis of side-chain¯exibility effects is crucial at this stage, since the¯exible backbone method allows complete side-chain¯exibility as well.…”
Section: Predicting Stabilities: Flexible Versus Fixed Backbonesmentioning
confidence: 99%
See 3 more Smart Citations
“…A more common approach includes additional discrete rotamers at de®ned increments, for example at AE 15 or AE one standard deviation from the statistically derived rotamer value (Dahiyat & Mayo, 1996;Tuffery et al, 1991). For our analysis, we have also used a version of our ®xed backbone algorithm that incorporates a wide range of¯exibility into the side-chains, with ®ne sampling of side-chain dihedral angles (5 ) at almost all possible angles (Lazar et al, 1997). An analysis of side-chain¯exibility effects is crucial at this stage, since the¯exible backbone method allows complete side-chain¯exibility as well.…”
Section: Predicting Stabilities: Flexible Versus Fixed Backbonesmentioning
confidence: 99%
“…The ROC programs used in this report have been described (Desjarlais & Handel, 1995;Lazar et al, 1997). Brie¯y, a ®xed backbone structure and a list of core residues is read into the program, and side-chain identities and/or conformers for each core position are sampled from a rotamer library.…”
Section: Fixed Backbone Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in the context of all other loci, T4 lysozyme can tolerate a loss in stability of 7 kcal/mol as a result of the 10 methionine substitutions in its core and maintain its native structure. Other studies have shown that computer-designed hydrophobic cores of equal volume are not equal in stability but rather result in a range of stabilities (Desjarlais & Handel, 1995;Lazar et al, 1997).…”
Section: Discussionmentioning
confidence: 99%